What is the solution of 3x + 6 7x

2.16x (2x - 6) = 72 + 12x2 solution
6x (2x - 6) = 72 + 12x2
12x2 - 36x = 72 + 12x2 | - 12x2
-36x = 72 | : (-36)
x = -2 L = {-2}
Forum
2.2(x + 4) 2x - 12 = 0.5x (6 + 4x) solution
(x + 4) 2x - 12 = 0.5x (6 + 4x)
2x2 + 8x - 12 = 3x + 2x2 | - 2x2
8x - 12 = 3x | - 3x
5x - 12 = 0 | + 12
5x = 12 | : 5
x = 2.4 L = {2.4}
Forum
2.31.5x * (3x + 6) - 3x * (4 + 1.5x) = -7.5 solution
1.5x * (3x + 6) - 3x * (4 + 1.5x) = -7.5
4.5x2 + 9x - 12 - 4.5x2 = -7,5
9x - 12 = -7.5 | + 12
9x = 4.5 | : 9
x = 0.5 L = {0.5}
Forum
2.42 (2x - 5) 3x - 4x (3x + 2.5) + 10 = 0 solution
2 (2x - 5) 3x - 4x (3x + 2.5) + 10 = 0
12x2 - 30x - 12x2 - 10x + 10 = 0
-40x + 10 = 0 | - 10
-40x = -10 | : (-40)
x = 0.25 L = {0.25}
Forum
2.5(5x - 7) 2x + x2 - 12 = 4x (3 + 2x) + 3 (x2 – 4) solution
(5x - 7) 2x + x2 - 12 = 4x (3 + 2x) + 3 (x2 – 4)
10x2 - 14x + x2 - 12 = 12x + 8x2 + 3x2 – 12
2 - 14x - 12 =2 + 12x - 12
-14x - 12 = 12x - 12 | - 12x
-26x - 12 = -12 | + 12
-26x = 0 | : (-26)
x = 0 L = {0}
Forum
2.61.4x (x + 3) - 6 (x + 0.2) = 2x (3.2 + 0.7x) - 8.2x + 3 solution
1.4x (x + 3) - 6 (x + 0.2) = 2x (3.2 + 0.7x) - 8.2x + 3
1.4x2 + 4.2x - 6x - 1.2 = 6.4x + 1.4x2 - 8.2x
1.4x2 - 1.8x - 1.2 = 1.4x2 - 1.8x | - 1.4x2
-1.8x - 1.2 = -1.8x | + 1.8x
-1.2 = 0 L = {}
Forum
2.75x * (3x - 4) + 2 * (4x + 5) = (4x - 6) * 3x + 3x2 + 40 solution
5x * (3x - 4) + 2 * (4x + 5) = (4x - 6) * 3x + 3x2 + 40
15x2 - 20x + 8x + 10 = 12x2 - 18x + 3x2 + 40
15x2 - 12x + 10 = 15x2 - 18x + 40 | -15x2 + 18x
6x + 10 = 40 | - 10
6x = 30 | : 6
x = 5 L = {5}
Forum
The x2-Terms have to disappear! If not, you've made a mistake.